Dukungan Pasangan dalam Menyelesaikan Perkuliahan - Dedek Nafita Sari; Muhammad Nasir; Dedy Surya (Syifaul Qulub: Jurnal Bimbingan dan Konseling Islam, 2020)
Getting married is human nature and is a human effort to manifest themselves into perfect beings. Married attracts new problems, especially for students who are trying to get an education. This research aims to support the problems of young couples in completing their lectures. This qualitative research uses Bart Smet's (1994) social support theory. This research is located in the Faculty of Usuluddin Adab and Da'wah, Iain Langsa with a subject of 3 female students. Data collected through interview techniques are then analyzed with domain analysis to get a general and complete picture of the phenomenon. The results showed that the main causes of inhibition of lectures for students who had received academic problems were: repeating courses, no thesis titles, and economic problems such as no money when paying tuition fees. Social support provided by couples is support in the form of emotional support, support instruments, support, and appreciation support.